Meaning and Controversy within Chinese Ancestor Religion - Batairwa Kubuya, Paulin (Asian Christianity in the Diaspora, 2018)
Chinese practices related to ancestors have long been the subject of conflicting interpretations. These practices are rooted in the lived experience of practitioners, and therefore need be considered as embodied expressions of the quest for existential meaning. For practitioners, the achievement of existential meaning requires the inclusion, implication, and mediation of the ancestors. When gestures in ancestor rites are analyzed from this perspective it is possible to appreciate their essence as constitutive of "ancestor religion." This book uses an inquisitive method that investigates the discrepancies between foreign and local explanations, and proposes another hermeneutic framework for ancestor related praxes. .